Researching and writing dissertations in business and management - .; Wood, Roy C.; Clark, Mona A.; Riley, Michael (London : Thomson Learning, 2000)
This book contains a large number of research methods texts available, and several aimed at students of business and management.
Keywords: Business; Methodology; Academic dissertations; Business -- Research -- Methodology; Management -- Research -- Methodology; Dissertations, Academic